Hot Springs in the Malay Peninsula - Chow, W.S (2010)
More than sixty hot springs have been discovered so far in the Malay Peninsula and all of the hot springs are genetically related to tectonic activities. Most of the sources are located along the western flank of the Main Range Granite Batholith and concentrated along major fault zones. A few hot springs however, are located within sedimentary rocks which are in close contact with the granite batholith or along the granite-sedimentary rock contact. The temperatures of the hot springs are less than 100oC at surface. The flow rates of most hot springs ranged from 2 to 6 litres/second, except for the one at Tambun (Perak) which has a flow rate of about 20 litres/second,. The hot springs are mostly located at low elevations ranging from 3 meters to 200 meters above sea level in a variety of geographic environments such as along stream beds or emerging such as along cracks in bedrock surfaces or in swampy areas. Chemical analysis of water from these hot springs showed that about 84% of the samples have high concentrations of F, and Na exceeding the permissible International Standards for drinking water. Samples from a few sites also have high concentrations of As. Seventeen sites emit a faint to strong H2S odour. Only two of these hot springs meet all the requirements for drinking and mineral water A large number of these hot springs, especially those that are easily accessible and in the vicinity of urban centers are turned into recreational resorts with hotels, hot spas, and swimming pools. None of these hot springs has been utilized for use as a source of geothermal energy and more investigations need to be carried out.